Polyurethane modified cold mix asphalt road patching (pu-asphalt patching) - Ahmad Nazri, Ahmad Syafiq Iskandar; Haieral, Ainnur Insyirah; Maizan, Nur Mardiyana; Che Lat, Diana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The durability of cold mix asphalt continues to pose challenges in road patching applications, especially under real-world environmental conditions. PU-Modified Asphalt is an innovative solution designed to address the durability challenges of conventional cold mix asphalt (CMA), which is prone to cracking, rutting, and moisture damage, resulting in frequent maintenance and higher costs. Combining polyurethane (PU) with traditional asphalt, it enhances the mechanical properties such as tensile strength, elasticity, and bonding strength. The material is developed using customizable polyol-to-isocyanate ratios to optimize performance and adaptability for diverse applications. The main advantages of PU-Modified Asphalt include better durability, exceptional moisture resistance, and reduced maintenance, ensuring longer-lasting and safer roads. Its eco-friendly design, which lowers resource consumption and carbon emissions, aligns with sustainability goals. This innovation offers significant socioeconomic benefits by reducing traffic disruptions, improving road safety, and lowering long-term maintenance costs. By offering cost-effective and high-performance solutions, PU-Modified Asphalt has the potential to transform road infrastructure, driving economic growth while supporting environmental preservation.